2009
DOI: 10.1186/bcr2326
|View full text |Cite
|
Sign up to set email alerts
|

Full-length cytokeratin-19 is released by human tumor cells: a potential role in metastatic progression of breast cancer

Abstract: Introduction We evaluated whether CK19, one of the main cytoskeleton proteins of epithelial cells, is released as full-length protein from viable tumor cells and whether this property is relevant for metastatic progression in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 37 publications
(48 reference statements)
2
98
1
1
Order By: Relevance
“…the concept involving the release of cKs from cells as an apoptotic or necrotic tumor cell death-associated mechanism no longer includes the early evidence of the production and secretion of these proteins as proliferation antigens by intact cells (6). additionally and in contrast to this common view that cKs are only released in fragmented forms by epithelial cells as a result of necrosis/apoptosis, evidence for the release of full-length cK19 by viable epithelial tumor cells in an active export process was provided in a recent report (3). in this study, cK19-releasing cells were detectable in Bm of 44-70% of breast cancer patients and were correlated to the presence of overt metastases.…”
Section: Cytokeratins As Markers Of Proliferating or Dying Tumor Cells?contrasting
confidence: 38%
“…the concept involving the release of cKs from cells as an apoptotic or necrotic tumor cell death-associated mechanism no longer includes the early evidence of the production and secretion of these proteins as proliferation antigens by intact cells (6). additionally and in contrast to this common view that cKs are only released in fragmented forms by epithelial cells as a result of necrosis/apoptosis, evidence for the release of full-length cK19 by viable epithelial tumor cells in an active export process was provided in a recent report (3). in this study, cK19-releasing cells were detectable in Bm of 44-70% of breast cancer patients and were correlated to the presence of overt metastases.…”
Section: Cytokeratins As Markers Of Proliferating or Dying Tumor Cells?contrasting
confidence: 38%
“…Immunohistochemistry utilizes labeled monoclonal antibodies directed against epithelial or tumor-associated antigens and automated digital microscopy or flow cytometry to isolate and count CTCs (Alix-Panabieres et al, 2008;Pantel et al, 2009;Allen & Keeney, 2010). This method allows identification of intact tumor cells occurring in the periphery for further characterization (Smirnov et al, 2005;Cohen et al, 2006).…”
Section: Detection Of Dtcs By Immunohistochemical Methodsmentioning
confidence: 99%
“…The demonstration of elevated levels of both ccCK18 and M65 in venous blood from tumors of endometrial cancer patients proved that these proteins were derived from the malignant tissue (Kramer et al, 2004). Additionally, and in contrast to the assumption t h a t C K s a r e o n l y r e l e a s e d i n f r a g m e n t e d f o r m b y e p i t h e l i a l c e l l s a s a r e s u l t o f necrosis/apoptosis, evidence for the active release of full-length CK19 by viable epithelial tumor cells was published (Alix-Panabieres et al, 2009). According to this study CK19-releasing cells were detected in BM of 44-70% of breast cancer patients and correlated to the presence of manifest metastases.…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that CK19-EPISPOT was more sensitive than CK19-ELISA. This incidence and number of CK19-releasing cells (RCs) were correlated to overt metastases and reduced patient survival (Alix-Panabieres et al, 2009). The author also applied a novel ELISPOT assay (designated "EPISPOT"), which detects viable CTC/DTC protein fingerprint from single epithelial cancer cells, for CK19 and mucin-1 (MUC1) in breast cancer, and fibroblast growth factor-2 (FGF2) in prostate cancer (Alix-Panabieres, 2012).…”
Section: Liquid Biopsies In Tumour Diagnosis and Treatmentmentioning
confidence: 99%